The Unexpected Diagnosis of Hepatic Tuberculosis in an Immunocompetent Patient - Nikolaos Garmpis; Christos Damaskos; Anna Garmpi; Aliki Liakea; Dimitrios Mantas (Case Reports in Surgery)
Background/Aim. Tuberculosis (TB) is a chronic infectious disease which affects millions. The most affected system is the respiratory. Thus, hepatic TB (HTB) without involvement of other organs is not common. Its clinical manifestations are not specific, and both imaging and histopathological findings are necessary for the diagnosis. The differential diagnosis includes primary and metastatic liver malignancies. Our aim is to describe the rare entity of HTB via a case presentation. Patient and Methods. We report a case of a 50-year-old female with abdominal pain, weight loss, fever, and anorexia. All imaging methods described a liver lesion. She underwent right lobe hepatectomy, and the histological evaluation demonstrated granuloma with central caseous necrosis. Results. Seven months postoperatively, the patient remains fit and healthy. Conclusion. HTB is a rare entity with no specific symptoms, signs, and no laboratory nor imaging findings. It can be managed effectively if diagnosed in time or lead to death if left untreated.